IMPLEMENTASI DIGITAL MARKETING PADA BUMDES MEKAR SEJAHTERA DENGAN CRITICAL SUCCESS FAKTOR DAN VALUE CHAIN - Reza, Reza kurnia lesmana; Suendri (Jurnal Sistem Informasi, 2024)
The implementation of Digital Marketing in Village-Owned Enterprises (BUMDes) Mekar Sejahtera aims to improve marketing performance and business competitiveness through the implementation of Critical Success Factors (CSF) and Value Chain. The study identifies and analyzes the key elements that influence the successful implementation of digital marketing strategies, as well as integrating them in a structured framework. In this study, data collection was carried out using two types of data: primary data and secondary data. Primary data was obtained through direct interviews and surveys with managers of Mekar Sejahtera BUMDes, while secondary data was obtained through analysis of relevant literature and similar case studies from other BUMDes that have implemented digital marketing. The research method used in this study is a qualitative method, which is a research approach used to understand social phenomena in a deep and descriptive way, focusing on the meaning contained in it. The results of the study show that there are several important factors that greatly affect the success of digital marketing in BUMDes Mekar Sejahtera, including: adequate technological infrastructure, competent human resources, effective content management, and appropriate promotion strategies. In addition, the integration of the value chain, starting from raw material procurement, production, distribution, to customer service, also plays an important role in improving the efficiency and effectiveness of digital marketing. The implementation of good digital marketing can increase the visibility of BUMDes Mekar Sejahtera products, expand market reach, and increase sales. However, the challenges faced include budget constraints, resistance to change, and the need for ongoing training for managers. Therefore, strategic recommendations include the development of adequate digital infrastructure, increasing the capacity of human resources through training and mentoring, and strengthening collaboration with external parties such as the government and the private sector. This study concludes that the application of CSF and Value Chain in the development of digital marketing in BUMDes Mekar Sejahtera can have a significant positive impact, as long as it is carried out with careful planning and consistent execution. This research is expected to be a reference for other BUMDes in adopting effective and sustainable digital marketing strategies. Keywords: Critical Succes Factor, Value Chain, Digital Marketing.